2017
DOI: 10.7448/ias.20.1.21498
|View full text |Cite
|
Sign up to set email alerts
|

“Now that you are circumcised, you cannot have first sex with your wife”: post circumcision sexual behaviours and beliefs among men in Wakiso district, Uganda

Abstract: Introduction: Safe male circumcision is an important biomedical intervention in the comprehensive HIV prevention programmes implemented in 14 sub-Saharan African countries with high HIV prevalence. To sustain its partial protective benefit, it is important that perceived reduced HIV risk does not lead to behavioural risk compensation among circumcised men and their sexual partners. This study explored beliefs that may influence post circumcision sexual behaviours among circumcised men in a programme setting.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In our study, having a higher level of education was a risk factor for unsafe sex. Inconsistent with our results, some studies with non-prisoners indicate that a low level of education is a significant risk factor for high-risk sexual behaviors (Kibira et al, 2017;Taffa, 1998). Hence, it appears that sexual behaviors among highly educated prisoners are different from those among the general population.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, having a higher level of education was a risk factor for unsafe sex. Inconsistent with our results, some studies with non-prisoners indicate that a low level of education is a significant risk factor for high-risk sexual behaviors (Kibira et al, 2017;Taffa, 1998). Hence, it appears that sexual behaviors among highly educated prisoners are different from those among the general population.…”
Section: Discussionsupporting
confidence: 84%
“…60 Findings from this meta-analysis are largely consistent with previous qualitative research on the same topic, with most men reporting that they adopt protective sexual behaviours (increase condom use or reduce the number of sexual partners) or maintained protective sexual behaviours after circumcision. [61][62][63][64][65] However, some studies reported that circumcised men increased higherrisk sexual behaviours after circumcision because they falsely believed that MMC could offer complete protection from HIV infection, 16,66,67 and one study from Zambia reported that about 30-40% of women incorrectly believed MMC fully protects men from getting HIV. 68 In addition, some studies found that men were more likely to report higher-risk sexual behaviours after MMC or report false belief regarding the protective effect provided by circumcision if they had low levels of education, were married, had alcoholism, or had misconceptions regarding antiretroviral therapy; religious beliefs might also affect risk behaviour after MMC.…”
Section: Discussionmentioning
confidence: 99%
“…Added to this, smaller, qualitative, and survey-based studies provide greater context for how changes in behavior and attitudes post-medical male circumcision may affect risk behaviors [ 63 ]. For example, one study reported men engaging in unprotected sex too soon after VMMC due to cultural beliefs concerning sexual cleansing and/or misunderstandings related to what it meant to be fully healed [ 43 ]. Worryingly, a cross-sectional survey study conducted in Botswana, Namibia, and Swaziland found that 13% of young men and 10% of young women incorrectly believed that circumcision provides men with 100% protection from HIV [ 64 ].…”
Section: Methodsmentioning
confidence: 99%